(3JfejI eg`GQGJ GdJhGUd dOi Wad GdXd hYdGbJg HJMSjf egGQGJ GdSdhc GdJhGabi dOi GdWad GdPGJhi GdeOeL (B/ s - (3eMehO YHOGdQDa YHOGdYGd eMeO SdWGfs; (3NGdO YHOGdQGRb GdfLGQ (B: s; (3gHI GSeGYjd eJhdi (B: s ((3GdbGgQI (B: s (3eMehO YHOGdQDa YHOGdYGd eMeO SdWGf (B: s, 2021)
(3gOa GdHMK Gdi JfejI egGQGJ GdJhGUd dOi Wa`d GdX`d h eOi JGKjQ Pdc Ydi GdSdhc GdJhGabi dOi GdWa`d GdPGJhi GdeOeL OGNd eOGQS GdOeL(B. (3MjK JchfJ YjfI GdHMK ef eLehYJj`f ef GdGWaGd (B( 8 ) (3KeGfjI GWaGd PGJhjjf eOeLjf h GdPjf JJQGhM GYeGQge GdRefjI Hjf (B(5: 7) (3SfhGJ, h jfWHb Ydjg TQhW GdOeL GdJYdjei GdeUQi h bhGYOg GdefXeI h GdJi JYJeO Ydi eYGjjQ eYGedGJ GdPcGA GdeMOOI eSHbG ddbHhd HeOGQS GdOeL GdPi jJQGhM Hjf (B(65: 84) (3Ydi ebjGS SJGfahQO HjfjI GdUhQI GdNGeSI(B: (3h ebjGS JbOjQ (B((3GdPGJhjI(B) (3ai GdWahdI (B((3Si Ejg CQ ES(B) (3WHbG dOQLI GdPGJhjI(B: (3h ebjGS GdSdhc GdJhGabi(B: (3h HQfGeL JfejI egGQGJ GdJhGUd dWad GdXd ddGWaGd GdYGOjjf(B: (3h (B(8) (3KeGfjI GWaGd ef GWaGd GdXd ef GdGbQGf GdYGOjjf(B: (3MjK GSaQJ fJGFL GdHMK Ydi eOi aGYdjI GSJNOGe HQfGeL JfejI egGQGJ GdJhGUd h YdGbJg HJMSjf GdSdhc GdJhGabi dOi GdWad GdPGJhi GdeOeLs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdJQHjI ddWahdI GdeHcQI (B- (3bSe GdYdhe GdfaSjIs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdJhGUds; (3GdSdhc GdJhGabis; (3Wad GdXds